Prevalence of rotavirus genotypes in South Korea in 1989-2009: implications for a nationwide rotavirus vaccine program - Van Thai Than; Wonyong Kim (Korean Pediatric Society, 2013)
The epidemiology of human group A rotavirus was analyzed by examining genotypic data acquired from 1989 to 2009 in South Korea. This information was derived from all the available published articles on rotavirus studies in South Korea, retrieved from both the PubMed and KoreaMed databases. Four common G types (G1, G2, G3, and G4) and three common P types (P[8], P[4], and P[6]) accounted for approximately 93% and 99% of the rotavirus reports, respectively. The G9 type was frequently detected after 2000, and because of this prevalence, it is considered to be the fifth most important G type rotavirus after the G1.G4 genotypes. Less common G types of the virus such as G12, G11, and G10 were detected in some geographic settings, and it is important to consider the context of these subtypes and their epidemiological significance. The P[9] virus genotype was observed in the study and has been discussed in many other studies; however, the P[3], P[10] and P[25] genotypes were rarely detected in the epidemiological research. In general, the distributions of the G and P genotypes showed temporal and geographical fluctuations, and a nationwide rotavirus vaccine program that targeted these genotypes demonstrated effectiveness in protecting against the circulating rotavirus strains. However, further analysis is needed to determine the true long-term effectiveness of these vaccines; the analysis should also consider the unexpected effects of vaccinations, such as vaccine-induced diseases, herd immunity, and changes in host susceptibilities.